The Effect Of Giving Green Tea To Elderly With Hypertension Disease To Decrease The Level Of Cholesterol At Tamban Baru Health Center - solikin solikin (UrbanGreen, 2020)
Background: High blood cholesterol levels lead to cholesterol deposits in blood vessels walls, the more sediment will clog blood vessels and disrupt blood circulation. This condition is the trigger of heart disease and stroke. To overcome the problems of high cholesterol in the blood, now it has begun to use natural ingredients to lower blood cholesterol levels that are the treatment by using herbal medicines such as medicines such as medicinal plants one of them is green tea. The main purpose the study is to know the effect of green tea on cholesterol values in elderly hypertensive patients in at Tamban baru community health centre in Tamban Baru Mekar Village. Methods: the research design used for this research is pre experimental one group, pretest and posttest design. The subject is elderly people with high cholesterol hypertension. Sampling technique in this research is purposive sampling technique with numbers of respondents 16 respondents who were given treatment. The research instrument used in this research is independent variable green tea giving and the dependent variable is cholesterol measures on elderly hypertensive patient using rapid test tool of cholesterol stick multi check in three, bivariate analysis using paired T test. Respondents were given green tea twice a day every morning and afternoon for 14 days